The gladiators from Capua - Lawrence, Caroline (London : Onion Children's Books, 2009)
Suspecting their friend Jonathan is alive, Flavia, Nubia, and Lupus go to Rome for the Colosseum Games, facing wild beasts, criminals, conspirators, and gladiators, and where Nubia is called upon to make a terrible choice.
Horn Book.
School Library Journal.
Horn Book, April 2006.
School Library Journal, February 2006.
5.0
5-8
Keywords: Colosseum (Rome, Italy) -- Juvenile fiction; Colosseum (Rome, Italy) -- Fiction; Colosseum (Rome, Italy) -- Fiction; Gladiators -- Juvenile fiction; Gladiators -- Fiction; Historical fiction; Mystery and detective stories; Gladiators -- Fiction; Historical fiction; Mystery fiction; Rome -- History -- Empire, 30 B.C.-476 A.D. -- Juvenile fiction; Rome -- History -- Empire, 30 B.C.-476 A.D. -- Fiction; Rome -- History -- Fiction; Historical fiction; Mystery fiction